Fabrication of a Functionally Generated, Implant-Retained Fixed Partial Denture - Alan J. Sutton, DDS, MS,1 Donald W. Sheets, Jr., DMD,2 and (Journal of Prosthodontics, 2003)
Partially edentulous patients are frequently restored with implant-supported restorations between and opposing natural teeth